Party Polarization, Ideological Sorting and the Emergence of the US Partisan Gender Gap. Issue 4 (5th October 2020) - Gillion, Daniel Q.; Ladd, Jonathan M.; Meredith, Marc
Abstract : This article argues that the modern American partisan gender gap – the tendency of men to identify more as Republicans and less as Democrats than women – emerged largely because of mass-level ideological party sorting. As the two major US political parties ideologically polarized at the elite level, the public gradually perceived this polarization and better sorted themselves into the parties that matched their policy preferences. Stable pre-existing policy differences between men and women caused this sorting to generate the modern US partisan gender gap. Because education is positively associated with awareness of elite party polarization, the partisan gender gap developed earlier and is consistently larger among those with college degrees. The study finds support for this argument from decades of American National Election Studies data and a new large dataset of decades of pooled individual-level Gallup survey responses.